2012
DOI: 10.1262/jrd.11-112h
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Development and Implantation Related Gene Expression of Oocyte Reconstructed with Bovine Trophoblast Cells

Abstract: Abstract. The temporal progressive increase of interferon tau (IFNτ) secretion from the bovine trophoblast is a major embryonic signal of establishing pregnancy. Here, we cultured and isolated bovine trophoblast cells (BTs) from IVM/IVF oocytes and in vitro produced blastocysts, used them, for the first time, as donor cells for nuclear transfer and compared them with adult fibroblasts (AFs) as donor cells. BTs were reprogrammed in enucleated oocytes to blastocysts with similar efficiency to AFs (14.5% and 15.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
1
15
1
Order By: Relevance
“…The presence of OCT4 mRNA in bovine and ovine trophoblasts detected in the present study and by others (Kurosaka et al, 2004; Degrelle et al, 2005; Berg et al, 2011; Saadeldin et al, 2012) contrasts with data from mouse trophoblasts, in which OCT4 expression is restricted to the ICM (Niwa et al, 2005). Berg et al (2011) showed that the upstream conserved region 4 (CR4) of OCT4 genes differs between bovine and murine species, and that bovine CR4 is effective for OCT4 expression in mouse TE.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The presence of OCT4 mRNA in bovine and ovine trophoblasts detected in the present study and by others (Kurosaka et al, 2004; Degrelle et al, 2005; Berg et al, 2011; Saadeldin et al, 2012) contrasts with data from mouse trophoblasts, in which OCT4 expression is restricted to the ICM (Niwa et al, 2005). Berg et al (2011) showed that the upstream conserved region 4 (CR4) of OCT4 genes differs between bovine and murine species, and that bovine CR4 is effective for OCT4 expression in mouse TE.…”
Section: Discussioncontrasting
confidence: 94%
“…According to Ezashi et al (2001), OCT4 expression subsides long before the initiation of conceptus elongation, when ETS2 begins to activate bovine IFNT gene transcription. In situ hybridization results suggested that OCT4 mRNA was restricted to the ICM in d 7 bovine blastocysts (Kurosaka et al, 2004; Saadeldin et al, 2012). However, further studies revealed that OCT4 expression remained until d 12 and 13, just prior to conceptus elongation (Degrelle et al, 2005), or even longer period (Berg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This protocol followed our previously published protocol [11]. Motile spermatozoa were obtained by purification using Percoll gradient method as previously described [13].…”
Section: Methodsmentioning
confidence: 99%
“…Two different feeders were used: the conventional method using mouse embryonic fibroblasts (MEFs) as we described before [11] and new feeder porcine granulosa cells (PGCs). PGCs were obtained through aspiration of follicular fluid of 4–6 mm porcine ovarian follicles with an 18-gauge needle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation